Perencanaan Instalasi Listrik dan Tata Udara Pasar Seng Bumiayu - Awaludin Fadilah; Sapto Nisworo; Deria Pravitasari (CV. Ulil Albab Corp, 2023)
Seng Bumiayu Market is a building that is still under construction, use and installation of electricity in the market building must be considered from the planning according to the Indonesian National Standard (SNI) and the General Electrical Installation Requirements (PUIL). the availability of electricity can be fulfilled optimally and the installation has been installed capable of supporting the operation of equipment that complies with standards so that security and safety can be guaranteed. The settlement method used to facilitate planning is collecting data, calculating and determining the characteristics of the building plan, determining load requirements, drawing a single line diagram, estimating the budget. The results of the calculation of the total load for lighting, exhaust fans and contact boxes are 13,327 watts, the selection of conductors and protection for lighting uses the NYM 2 x 2.5 mm2 type and the socket uses the NYM 3 x 2.5 mm2 type with MCB protection, the SDP panel uses type NYY 4 x 10 mm2 with MCCB safety and the voltage drop from the SDP panel to the load panel is 2.9 volts. Increasing the reliability and convenience of the installation system in the Seng Bumiayu Market building requires a generator set with a minimum power capacity of 15 kVA and calculating the budget for obtaining Rp. 600,000,000.-. The results of calculating load requirements, selection of conductors, safety requirements, voltage drop values ​​are in accordance with PUIL and SNI.